The Differential Effects of Attentional Focus in Children with Moderate and Profound Visual Impairments - McNamara, Scott W. T.; Becker, Kevin A.; Silliman-French, Lisa M. (Frontiers in Psychology, 2017)
It has been consistently reported that an external focus of attention leads to better motor performance than an internal focus, but no research to date has explored this effect in a population with visual impairments (VI). External focus statements typically reference something in the environment (e.g., target) that may be difficult to conceptualize for people with VI since they cannot generate a visual representation of the object of focus. Internal focus statements could be more closely identifiable with proprioception that is not impaired in this population. Recent studies have reported that sighted adults with temporarily obstructed vision are able to receive an external focus benefit when performing discrete tasks (i.e., golf putt, vertical jump), however it is unclear if those with VI would experience the same benefit. The purpose of this investigation was to compare how an internal focus and external focus impact the balance of children with VI. Eighteen children with VI were grouped into a moderate (n = 11) and a profound VI group (n = 7). Participants completed a familiarization trial, an internal focus trial (i.e., focusing on feet) and an external focus trial (i.e., focusing on markers) in a counterbalanced order. The moderate VI group had a lower root mean square error while using an external focus (p = .04), while the profound VI group did not differ between conditions (p > .05). These results suggest that while performing a task reliant on sensory feedback, an external focus benefit may be dependent on the severity of VI. Further research is needed to examine whether external focus statements can be presented in a way that may be more intuitive to those with profound VI. These findings may help to influence how professionals in health-related fields (e.g., physical therapist, physical educators) give instructions on motor performance to populations with VI.